An 8.0% Determination of the Baryon Fraction in the Intergalactic Medium from Localized Fast Radio Bursts - Wang, Bao; Wei, Jun-Jie (The Astrophysical journal, 2023)
The dispersion measure (DM)–redshift relation of fast radio bursts (FRBs) has been proposed as a potential new tool for probing the intergalactic medium (IGM) and for studying cosmology. However, poor knowledge of the baryon fraction in the IGM ( f IGM ) and its degeneracy with cosmological parameters impose restrictions on the cosmological applications of FRBs. Furthermore, DMs contributed by the IGM (DM IGM ) and host galaxy (DM host ), important cosmological quantities, cannot be exactly extracted from observations, which would bring uncontrolled systematic uncertainties in FRB cosmology. In this work, we use 17 localized FRBs to constrain f IGM and its possible redshift evolution. Other cosmological probes such as type Ia supernovae, baryon acoustic oscillations, and cosmic microwave background radiation are combined to break parameter degeneracy. Taking into account the probability distributions of DM IGM and DM host derived from the IllustrisTNG simulation, we obtain a robust measurement of f IGM = 0.927 ± 0.075, representing a precision of 8.0%. We find that there is no strong evidence for the redshift dependence of f IGM at the current observational data level. The rapid progress in localizing FRBs will significantly improve the constraints on f IGM .